Perlindungan kekayaan intelektual untuk produk Batik Palbatu: Meningkatkan daya saing dan keberlanjutan - Nugroho, Widyo; Setyawan, Aris Budi; Prajaka, Sandhi (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2025)
Palbatu Batik House operates in the creative industry, producing a variety of batik patterns. Unfortunately, none of its products have yet been protected by intellectual property rights. Intellectual property rights provide legal safeguards for the ownership of public and private intellectual property, fostering the development of the creative economy and playing a vital role in national development. This study examines the protection of Intellectual Property Rights (IPRs), specifically copyrights and industrial designs, for Palbatu Batik House, and to explore the registration of intellectual property rights for contemporary batik patterns on Palbatu Street. Employing a normative juridical approach, the research involves a review of relevant literature and legal sources. Secondary data forms the basis of this study, including primary legal materials, such as laws and regulations, and secondary materials from various articles and books. Findings indicate that Palbatu Batik House is eligible for Intellectual Property Rights (IPR) protection in the form of Copyrights and Industrial Design Rights, which will aid in safeguarding the originality of its products, enhancing the competitive edge of this Micro, Small, and Medium Enterprise (MSME).